Juridical Review of The Use of CCTV E-Tickets in Traffic is Linked to Human Rights and The Right to Privacy of a Person Under The Constitution 1945 - Monica, Tri; Sihombing, L. Alfies; Nuraeni, Yeni (Rechtsvinding, 2025)
This study aims to analyze the efficiency of CCTV usage in Indonesia’s E-Tilang system concerning traffic law enforcement and the protection of human rights, particularly the right to privacy as guaranteed under Article 28G(1) of the 1945 Constitution. The research employs a normative-empirical legal approach with descriptive-analytical methods. Data were collected through library research and interviews with police officials, the National Commission on Human Rights (Komnas HAM), and road users. Findings indicate that while E-Tilang effectively reduces traffic violations and minimizes extortion practices, it raises serious privacy concerns. Continuous CCTV surveillance without clear data retention limits, lack of transparency, and absence of post-enforcement data deletion mechanisms risk violating the purpose limitation and data minimization principles under Indonesia’s Personal Data Protection Law No. 27/2022. Therefore, regulatory reform based on privacy by design principles is essential, including establishing an independent oversight authority and enhancing public participation.